Penerapan Problem Based Learning pada Pembuatan Pola Rok Lipit Hadap di Fase E Tata Busana SMKN 1 Bagor - Nike Fatma Rahmawati; Mein Kharnolis; Marniati Marniati; Ma’rifatun Nashikhah (Departement of Mathematics Education, 2024)
This research aims to describe the process of implementing Problem Based Learning, responses and student learning outcomes after implementing Problem Based Learning. This research was carried out at SMKN 1 Bagor in 2023/2024, on learning outcomes for making pleated skirt patterns. The subjects of this research were 36 students of class X Clothing 1. The data collection methods used were observation, questionnaires and assessment rubrics. The data analysis technique used is quantitative descriptive. The results of the research show that the implementation of Problem Based Learning in making pleated skirt patterns received a very good category. Student responses after implementing Problem Based Learning obtained a positive category where students responded well to learning. The learning outcomes of students in making pleated skirt patterns meet the Criteria for Completion of Learning Objectives namely 70.